ANALISIS PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) TELLER PADA PELAYANAN NASABAH DI KJKS BMT AGAM MADANI KOTO TUO - Fitri Utama; Dewi Manda Anggraini (Jurnal Ekonomi dan Bisnis, 2025)
This research was motivated by problems with the teller Standard Operating Procedures (SOP) at KJKS BMT Agam Madani Koto Tuo, where customers complained that the service provided by the tellers took a very long time and was not dexterous. There are long queues because there are not enough seats in the waiting room, or problems with the system occur when people try to pay, even though not many people are using the service. The author used both primary and secondary materials to structure his research, which followed a qualitative methodology. Apart from that, methods of collecting information are through documentation, interviews and direct observation. Collecting data, cleaning it, displaying it, and generating conclusions are steps in the data analysis process. The research and analysis carried out by the author led to the conclusion that the BMT Standard Operating Procedures (SOP) have been implemented eflectively. The teller has done a good job, providing customers with timely service that doesn't make them feel uncomfortable. feel comfortable using the services oflered by tellers when making cash deposits and withdrawals. Tellers at KJKS BMT Agam Madani Koto Tuo provide good service and most customers are satisfied. However, some customers complained that teller transaction services were slow, causing them to have to queue for a long time. Implementing monitoring, training and communication programs is critical to ensuring that services comply with Standard Operating Procedures (SOPs). Apart from that, tellers must also be friendly, smiling and gentle and understand their duties and responsibilities to provide good service.